Effects of creatine supplementation on athletic performance in soccer players: A systematic review and meta-analysis - Mielgo-Ayuso, J.; Calleja-Gonzalez, J.; Marqués-Jiménez, D.; Caballero-Garcia, A.; Córdova, A.; Fernández-Lázaro, D. (Nutrients, 2019)
Studies have shown that creatine supplementation increases intramuscular creatine concentrations, favoring the energy system of phosphagens, which may help explain the observed improvements in high-intensity exercise performance. However, research on physical performance in soccer has shown controversial results, in part because the energy system used is not taken into account. The main aim of this investigation was to perform a systematic review and meta-analysis to determine the efficacy of creatine supplementation for increasing performance in skills related to soccer depending upon the type of metabolism used (aerobic, phosphagen, and anaerobic metabolism). A structured search was carried out following the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guidelines in the Medline/PubMed and Web of Science, Cochrane Library, and Scopus databases until January 2019. The search included studies with a double-blind and randomized experimental design in which creatine supplementation was compared to an identical placebo situation (dose, duration, timing, and drug appearance). There were no filters applied to the soccer players` level, gender, or age. A final meta-analysis was performed using the random effects model and pooled standardized mean differences (SMD) (Hedges`s g). Nine studies published were included in the meta-analysis. This revealed that creatine supplementation did not present beneficial effects on aerobic performance tests (SMD, -0.05; 95% confidence interval (CI), -0.37 to 0.28; p = 0.78) and phosphagen metabolism performance tests (strength, single jump, single sprint, and agility tests: SMD, 0.21; 95% CI, -0.03 to 0.45; p = 0.08). However, creatine supplementation showed beneficial effects on anaerobic performance tests (SMD, 1.23; 95% CI, 0.55-1.91; p <0.001). Concretely, creatine demonstrated a large and significant effect on Wingate test performance (SMD, 2.26; 95% CI, 1.40-3.11; p <0.001). In conclusion, creatine supplementation with a loading dose of 20-30 g/day, divided 3-4 times per day, ingested for 6 to 7 days, and followed by 5 g/day for 9 weeks or with a low dose of 3 mg/kg/day for 14 days presents positive effects on improving physical performance tests related to anaerobic metabolism, especially anaerobic power, in soccer players.